2020
DOI: 10.1038/s41467-020-16309-2
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for Argonaute 2 in EGFR-KRAS signaling in pancreatic cancer development

Abstract: Both KRAS and EGFR are essential mediators of pancreatic cancer development and interact with Argonaute 2 (AGO2) to perturb its function. Here, in a mouse model of mutant KRAS-driven pancreatic cancer, loss of AGO2 allows precursor lesion (PanIN) formation yet prevents progression to pancreatic ductal adenocarcinoma (PDAC). Precursor lesions with AGO2 ablation undergo oncogene-induced senescence with altered microRNA expression and EGFR/RAS signaling, bypassed by loss of p53. In mouse and human pancreatic tiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 70 publications
4
39
0
Order By: Relevance
“…Mediates oncogenic activity of miR-10a [17] Recruites RNA Polymerase II to promoters of cancer related genes [18][19][20] Silencing inhibits hepatocellular carcinoma cells growth and migration [21] Silences interferon induced apoptosis via scattering of dsRNAs in breast cancer cells [22] Necessary for differentiation of leukaemia cells upon treatment with retinoic acid [23] Represses VEGF expression and vascularization under hypoxic stress [24] Mediates suppressive activity of miR-145-5p [25] Silencing inhibits growth of hypopharyngeal cancer cells [26] Stabilizes MYC mRNA stability [27] Enhances the activity of mutant KRAS protein [28,29] Overexpression results in decreased proliferation and motility of lung cancer cells [30] Interacts with ERβ receptor [31] Required for differentiation of leukaemia cells upon treatment with 1,25-dihydroxyvitamin D [32] Recruits Rad51, MMSET and KAT5 to DNA breaks [33,34] Enhances angiogenesis [35,36] Promotes telomerase activity [37]…”
Section: Ago1mentioning
confidence: 99%
See 4 more Smart Citations
“…Mediates oncogenic activity of miR-10a [17] Recruites RNA Polymerase II to promoters of cancer related genes [18][19][20] Silencing inhibits hepatocellular carcinoma cells growth and migration [21] Silences interferon induced apoptosis via scattering of dsRNAs in breast cancer cells [22] Necessary for differentiation of leukaemia cells upon treatment with retinoic acid [23] Represses VEGF expression and vascularization under hypoxic stress [24] Mediates suppressive activity of miR-145-5p [25] Silencing inhibits growth of hypopharyngeal cancer cells [26] Stabilizes MYC mRNA stability [27] Enhances the activity of mutant KRAS protein [28,29] Overexpression results in decreased proliferation and motility of lung cancer cells [30] Interacts with ERβ receptor [31] Required for differentiation of leukaemia cells upon treatment with 1,25-dihydroxyvitamin D [32] Recruits Rad51, MMSET and KAT5 to DNA breaks [33,34] Enhances angiogenesis [35,36] Promotes telomerase activity [37]…”
Section: Ago1mentioning
confidence: 99%
“…The interaction markedly contributed to cytotoxicity of the drugs [ 60 ]. Furthermore, AGO2 was found to be an important binding partner of the protein product of KRAS , a well-characterized oncogene ( Figure 2 b) [ 28 , 29 ]. It was shown that high levels of AGO2 protein enhanced neoplastic transformation driven by KRAS mutants, whereas knockout of AGO2 resulted in the growth arrest of KRAS-dependent cancer cells [ 28 ].…”
Section: The Involvement Of Ago Proteins In Tumor Associated Procementioning
confidence: 99%
See 3 more Smart Citations